Hadith #3397 - Sunan Abi Dawud - Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Usayd bin Zuhayr bin Rafi' (Sunan Abi Dawud)
AbuRafi’ came to us from the Messenger of Allah (ﷺ) said: The Messenger of Allah (ﷺ) forbade us from a work which benefited us; but obedience to Allah and His Apostle (ﷺ) is more beneficial to us. He forbade that one of us cultivates land except the one which he owns or the land which a man lends him (to cultivate).
Grade: Sahih